Corporate ownership structure and audit fees : evidence from Malaysian listed companies on Bursa Malaysia - Nurul Farha binti Mohamed Rusdi (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2013)
The increasing focus on the impact of different ownership structures is prompted by the existence of monitoring differences by shareholders on corporate affairs including the financial reporting process. The external auditors' reliance on the corporate internal control varies according to the different ownership structures with a concomitant variation in the fees charged to their clients. A number of corporate collapses worldwide have highlighted the need for strong corporate governance to strengthen the financial reporting process with an emphasis on audit quality. The purpose of this study is to investigate the association between corporate ownership structures and audit fees paid to external auditors by Malaysian companies listed on Bursa Malaysia. This study focuses on the extent of the auditor's reliance on the client's internal control inasmuch as the corporate ownership structures are varied, and, ultimately, affect the audit fees. This study applies the agency theory in formulating three hypotheses that guide the results analysis. By employing a multi regression model for a sample of 345 Malaysian companies listed on Bursa Malaysia, this study examines the relationship of ownership structure, namely, managerial ownership, foreign ownership and government ownership with audit fees using data for 2010. The results show a significant positive relationship between audit fees and firms with larger foreign ownership and government ownership but no significant relationship with firms with higher managerial ownership. This study contributes recent evidence concerning the relationship between corporate ownership structure and audit fees. The regulator may consider ownership structure on the standards or regulation setting in order to be practical and operationalized in line with the impact associated with different ownership structures. The practitioners may also design appropriate methodologies and procedures for the different ownership structures for high quality service and to standardize the risk mitigation process.